Narrativas sobre el establecimiento de la relación de pareja, la infidelidad y la familia de origen en personas con orientación homosexual (2021)
This research seeks to publicize, through narratives, aspects of the establishment of a couple, infidelity and the intervention of the family of origin in homosexual people between 35 and 45 years old. A review of the literature was carried out, which proved important to address the different topics of the research such as: couple relationship, infidelity, sexual and emotional infidelity, adulthood, among other things.